Pengaruh HCSQ Terhadap Behavioral Intention Melalui Experience Economy Dan Emotional Satisfaction - Choliq, Sheila Soraya; Suryaningsih, Ika Barokah; Prasetyo, Aris (ARTERI : Jurnal Ilmu Kesehatan, 2024)
The average outpatient waiting time for Specialist Outpatient Clinic at Citra Husada Hospital Jember is 88 minutes. This is less than the minimum hospital service standard. This study aims to determine the effect of Healthcare Service Quality on Behavioral Intention through Experience Economy and Emotional Satisfaction as intervening variables in specialist outpatient clinics at Citra Husada Hospital, Jember. The population in this study were all specialist outpatients at Citra Husada Hospital, Jember. The sampling method used in this research was Purposive Sampling. Based on the determination of the number of samples used in this research, there were 120 Specialist Poly Outpatients at Citra Husada Hospital, Jember. Data collection and collection procedures: The research was carried out by distributing a questionnaire which was a list of statements to be answered by respondents, namely Outpatient Specialist Polyclinics at Citra Husada Hospital, Jember. The data analysis method used in this research is the Structual Equation Model (SEM) with the SmartPLS application. The results of the research show that the quality of health services is getting better, the economic experience and emotional satisfaction, and the specialist poly outpatients at Citra Husada Hospital in Jember are getting better. The better the Healthcare Service Quality, Experience Economy and Emotional Satisfaction, the better the Behavioral Intention of Specialist Poly Outpatient Patients at Citra Husada Hospital, Jember. Suggestions for further research could be to assess the quality of health services from the perspective of health service providers, how they distribute the services provided compared to evaluations from patients and competitors so that the assessment of the quality of health services becomes more comprehensive